Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session "Perinatal neurologic disorders and their long-term impact on development. Ethical issues" - - (Hygeia Press di Corridori Marinella, 2018)
Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session "Perinatal neurologic disorders and their long-term impact on development. Ethical issues" ABS 1. QUALITATIVE CEREBRAL ABNORMALITIES AT TERM MRI IN THE PREMATURE INFANT AND CORRELATION WITH PREVIOUS CUS FINDINGS AND NEURODEVELOPMENTAL OUTCOME COMPONENTS AT 24 MONTHS OF CORRECTED GESTATIONAL AGE • K. Chatzidimitriou, A. Chebsey, D. Odd, M. El Brookle, M. Likeman, A. Heep ABS 2. ASSOCIATION OF IUGR AND OTHER BASELINE CHARACTERISTICS WITH BRAIN INJURY AND NEURODEVELOPMENTAL OUTCOME AT 24 MONTHS OF CORRECTED GESTATIONAL AGE IN A PREMATURE INFANT COHORT • K. Chatzidimitriou, A. Chebsey, D. Odd, M. El Brookle, M. Likeman, A. Heep ABS 3. NEONATAL SEIZURES: A RETROSPECTIVE STUDY OF 146 CASES IN A NICU IN TUNISIA • H. Ben Hamida, F.Z. Chioukh, T. Khemis, N. Djobbi, K. Ben Ameur, C. Hafsa, M. Doggui, M. Bizid, K. Monastiri ABS 4. ANTENATAL AND POSTNATAL RISK FACTORS IN NEONATAL SEIZURES • F. Doandes, A. Manea, O. Costescu, D. Cioboata, N. Lungu, M. Boia ABS 5. CHANGES IN MORTALITY AMONG EXTREMELY PRETERM INFANTS IN THE SOUTH OF THAILAND: A 15-YEAR EXPERIENCE • W. Janjindamai, B. Thirapaleka, A. Thatrimontrichai, G. Maneenil, S. Dissaneevate ABS 6. INTRAVENTRICULAR HEMORRHAGE: RISK FACTORS AND PROGNOSIS IN VERY PRETERM INFANTS • A. Bezzine, R. Boukhris, Y. Mesbahi, B. Rabii, E. Ben Hamida, Z. Marrakchi ABS 7. NEONATAL ARTERIAL ISCHEMIC STROKE: A STUDY OF 14 CASES • A. Ben Thabet, F. Charfi, A. Ben Hamad, M. Charfi, Ch. Regaieg, N. Hamida, F. Kammoun, Ch. Triki, R. Regaieg, A. Bouraoui, A. Gargouri ABS 8. NEONATAL THERAPEUTIC HYPOTHERMIA IN LATVIA • S. Stanke, A. Jurasa, S. Laktina ABS 9. OUTCOME OF PYRIDOXINE-DEPENDENT EPILEPSY: A 14-CASE STUDY • A. Ben Thabet, F. Charfi, A. Ben Hamad, M. Charfi, Ch. Regaieg, N. Hamida, F. Kammoun, Ch. Triki, R. Regaieg, A. Bouraoui, A. Gargouri ABS 10. PERINATAL BRAIN INJURY AND DYNAMICS OF CLINICAL SYMPTOMATOLOGY • D. Šumanović-Glamuzina, M. Karlović, M. Jerković-Raguž, A. Mustapić ABS 11. THE ROLE OF RED BLOOD CELL TRANSFUSIONS IN THE PREVENTION OF SEVERE INTRA/PERIVENTRICULAR HEMORRHAGE • M. Boia, A. Manea, D. Cioboata, O. Costescu, F. Doandes, A. Hudisteanu ABS 12. PHENOTYPIC VARIABILITY OF CONGENITAL MYOTONIC DYSTROPHY: REPORT OF TWO CASES • A. Vontzalidis, K. Karachristou, E. Yatrakou, K. Kosma, K. Kekou, G.K. Papadimas, K. Katexi, A. Moutafi, V. Galiaki ABS 13. A CASE OF SEVERE NEUROMORBIDITY OF SURVIVOR TWIN AFTER INTRAUTERINE DEATH OF A CO-TWIN • M. Starcevic, N. Sindicic Dessardo, M. Ilijic Krpan ABS 14. COMPLICATIONS OF EXTERNAL VENTRICULAR DRAINAGE AND VENTRICULO-PERITONEAL SHUNT INSERTION IN POST-HEMORRHAGIC HYDROCEPHALUS • O. Costescu, A. Manea, F. Doandes, D. Cioboata, N. Lungu, M. Boia ABS 15. FETAL ANEUPLOIDY: ETHICAL ISSUES AND MANAGEMENT OPTIONS IN ONE OF THE FRATERNAL TWINS • M. Anciuc, D.C. Rac, M.C. Cucerea, C. Bănescu ABS 16. VESICULAR ERUPTION IN NEONATES: DIAGNOSTIC CHALLENGES • A. Hosu, S. Andreica, I. Ioana, M. Matyas, M. Hasmasanu, D. Rusu, S. Cotutiu, D. Morar-Huniadi, A. Baican, G. Zaharie